ROLE OF CULTURE AND LABOR PROTECTION IN PRODUCTION SAFETY - Kamalova Mahfiza Shamsidinovna , (European Journal of Life Safety and Stability (2660-9630), 2021)
The article describes the basics of culture formation in labor protection and its methodological approaches.